Educating the Whole Person: Creativity, Holism and the Future of Learning - Delgado Álvarez, Alberto (Revista Ensayos Pedagógicos, 2026)
Educating the whole person has become a central priority in contemporary educational reform, emphasizing creativity, holistic development, and the cultivation of competencies for an uncertain and challenging future. Rather than focusing exclusively on standardized knowledge acquisition, holistic education integrates cognitive, emotional, social, ethical, and cultural dimensions of learning. Creativity plays a pivotal role in this vision, fostering adaptability, problem-solving, and innovation across disciplines. There is a need to align curriculum, assessment, and quality assurance with broader educational purposes. Such alignment requires innovative assessment practices—performance tasks and reflective activities that capture process, originality, and collaboration. It also demands policies that promote individual equity, digital competence, and fair inclusion, ensuring that all learners benefit from creative opportunities. Educating the whole person is therefore both a pedagogical and societal imperative, preparing individuals not only for academic success but also for meaningful participation in civic, cultural, and global communities.